The Accra ConfessionAn example of the ecclesiological implications of public theology - Brinkman, Eduardus (Eddy) (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The report of the World Alliance of Reformed Churches (WARC) in Ghana in 2004 with the title The Accra Confession: Covenanting for Justice, has resonated within the Reformed churches worldwide. In this document, WARC, as an alliance of faith communities, reacts to the devastating effects of economic globalisation. It offers a faith perspective on a phenomenon, the negative consequences of which all people, but especially those in the global South, are experiencing. Following an extensive summary of the document, this article will reflect upon some ecclesiological implications and problems related to being a church that intends to speak out on social and public issues. In order to better understand the way Reformed churches tend to go public, a comparison will be made between the Accra document and a recent document issued by the Roman Catholic Church that also deals with public issues.